Assesment of Grip Strength of Community Dwelling Older People in Tenayan Raya Pekanbaru Indonesia, a Urban Area - Sumandar (Institute of Computer Science (IOCS), 2020)
Grip strength is related concurrently to measures other than the strength of different muscle actions, such measures are those of activities, involving the upper limbs, of which the hands are a part. Low level grip strength has shown strong to increase risks of morbidity and mortality in older people. The aim of this study was to analysis profile of grip strength. The study was a descriptive study, involving simultaneous data collection on profile of grip strenght. The respondents were 120 community-dwelling older people who urban area especially Tenayan Raya Distric Pekanbaru Indoensia. Cluster sampling was used to recruit the samples. Majority age were 63.10 years old. For gender, can be seen that female was 68.3 %, male was 31.7 % and marital status show 78.3 % was married, Widower were 21.7%, not available for no married or 0 %. For educational level showed that Diploma/Bachelor/master were 29,2 %, Senior High School was 35.8 %, Elementary school was 21.7 %, junior high school was 13.3 %. For employed status show that unemployed was 71.7%, older people with employed was 28.3 %. For assessment of grip strength show that 58.3 % was low and just found normal was 41.7 %. This research to help geriatric nurse enhance education and health promotion through handgrip strength examination. By getting handgrip strength condition will impact to health behavior